2007
DOI: 10.1111/j.1365-2036.2007.03586.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and cytokines in non‐alcoholic fatty liver disease

Abstract: SUMMARY BackgroundSeveral adipocytokines have been implicated in the pathogenesis nonalcoholic fatty liver disease (NAFLD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
329
2
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(370 citation statements)
references
References 29 publications
(44 reference statements)
19
329
2
14
Order By: Relevance
“…24 whereas others have shown lower resistin levels in NASH versus simple fatty liver. 25 In our study, resistin levels increased significantly in the subjects receiving orlistat. Additionally, a significant correlation was found between resistin levels and weight loss.…”
Section: Discussionmentioning
confidence: 61%
“…24 whereas others have shown lower resistin levels in NASH versus simple fatty liver. 25 In our study, resistin levels increased significantly in the subjects receiving orlistat. Additionally, a significant correlation was found between resistin levels and weight loss.…”
Section: Discussionmentioning
confidence: 61%
“…17 The complex role of visceral adipocytes as an important source of cytokines, adipokines and para-endocrine substances may be involved. 44,45 Routine biochemical and histological parameters of inflammation, however, showed no significant differences or correlations in this study cohort.…”
Section: Discussionmentioning
confidence: 69%
“…A few studies have reported that serum resistin levels did not differ between patients with NAFLD and without the disease [92,93]. However, one study has shown that excessive ectopic accumulation of fat in the liver and skeletal muscle of insulin-resistant subjects is associated with lower concentrations of resistin in the serum, while another reports increased levels of resistin, but only in patients with severe liver disease [94,95].…”
Section: Resistin and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%